HUBUNGAN PENGETAHUAN, KEPATUHAN DAN KETERSEDIAAN FASILITAS DENGAN MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3RS) PADA TENAGA PERAWAT DI RS X KOTA BATAM TAHUN 2026 - Siti Mulya Ripah; Wan Intan Parisma; Noviyanti Noviyanti (Bajang Institute, 2026)
Abstract: Hospitals are high-risk work environments for nurses due to exposure to biological, chemical, and physical hazards. The objective of this study is to analyze the relationship between knowledge, compliance, and the availability of facilities with Occupational Safety and Health (OSH) risk management at Hospital X in Batam City in 2026. This is a quantitative study using an analytical observational method with a cross-sectional approach, involving 87 respondents through total sampling. The study utilized a questionnaire as the research instrument, and data analysis was performed using the Chi-Square test. The results, obtained from the Chi-Square test, indicate a significant relationship between knowledge (p-value 0.039 < α = 0.05), compliance (p-value 0.000 < α = 0.05), and facility availability (p-value 0.000 < α = 0.05) and OSH risk management. It is concluded that these three variables are significantly associated with Hospital Occupational Safety and Health Risk Management (OSH). It is recommended that hospitals continuously improve education and training related to OSH Risk Management.